THE NEGOTIATION BETWEEN QUEER SPECTATORSHIP AND QUEER TEXT ON RIRI RIZA’S SOE HOK GIE - Maimunah, Maimunah (ATAVISME, 2010)
The emergence of young generation filmmakers who are more confident in depicting gender and sexual issues after the Soeharto era (1998), significantly changes the construction of sexual diversity in 2003-2006 Indonesian films. One of the considerable phenomena is the personal experience and social commitment to support sexual minorities such as gay and lesbian issues. At the same time Indonesian queer communities strive to read the discourse of homosexuality in different way. Physical contact and even intimacy between persons of the same-sex, in both public and private spaces, was common practice in Indonesian cultures, and did not carry any suggestion of homoerotic desire. In this Riri Riza?s film, Soe Hok Gie, however, cinematic technique, narrative and dialogue all contribute to an eroticising of same-sex relationships that is particularly perceptible in cultures that previously regarded physical and emotional interactions between persons of the same-sex as unremarkable. This article based on Benshoff and Griffin?s (2006) theory on queer film. Abstrak: Perkembangan film Indonesia setelah tumbangnya rezim Soeharto menunjukkan adanya fenomena di kalangan sutradara muda untuk mengeksplorasi tema tentang gender dan seksualitas. Isu tentang seksual minoritas seperti seksualitas gay dan lesbian adalah salah satu ciri yang cukup menonjol dalam film-film yang diproduksi setelah tahun 2003. Pada saat yang sama, penonton queer (seksualitas nonnormatif) terutama yang berasal dari komunitas queer membaca scene sebuah film terutama yang menampilkan kontak fisik dan keintiman antara orang-orang sesama jenis dengan cara yang baru. Dalam tradisi budaya Indonesia, kontak fisik dan keintiman itu tidak diterjemahkan dalam sebuah hubungan homoerotika . Pembacaan yang berbeda ditunjukkan pembaca dalam film Soe Hok Gie karya Riri Riza. Artikel ini menggunakan teori Queer Film yang dikemukakan oleh Benshoff dan Griffin (2006). Kata-Kata Kunci: queer spectatorship, homoerotisisme, Soe Hok Gie